Combination of an Efficient Photochemical Vapor Generation System and Flame Atomic Absorption Spectrophotometry for Trace Nickel Determination in Wastewater Samples - Buyukpinar, Cagdas; San, Nevim; Komesli, Okan T.; Bakirdere, Sezgin (TAYLOR & FRANCIS INC, 2021)
A photochemical vapor generation - atomic absorption spectrometry combination was applied for the determination of nickel. Optimizations of low molecular weight organic acid type, concentration of low molecular weight organic acid, ultraviolet irradiation period, mixing type and period, flow rate of carrier gas, and temperature of atomizer were conducted in order to maximize analytical signals. Under the optimum conditions, analytical performance of the photochemical vapor generation - atomic absorption spectrometry system was evaluated; the limits of detection and quantification were determined to be 3.5 and 11.6 mu g/L, respectively. Spiking experiments were carried out in wastewater samples to investigate the applicability and accuracy of the developed method. Matrix matching calibration was used to calculate the recovery since negative matrix effects (approximately 45%) were observed on the analyte with external calibration. The recovery results for 40, 60 and 80 mu g/L of spiked concentration were determined to be 106.2%, 101.4% and 99.0%, respectively, indicating the high accuracy of the developed method for the selected matrix.
Keywords: Atomic absorption spectrophotometry; nickel; photochemical vapor generation; wastewater; SOLID-PHASE EXTRACTION; MODIFIED MAGNETIC NANOPARTICLES; MICROEXTRACTION METHOD; PRECONCENTRATION; NI(II); FOOD; MICROWAVE; COBALT; CU(II); PB; Chemistry